Synthesis of Hollow ZnSnO3 Nanospheres with High Ethanol Sensing Properties. (24th October 2016) - Wang, Qiong; Yao, Na; Liu, Chen; An, Dongmin; Li, Yan; Zou, Yunling; Tong, Xiaoqiang
Abstract : Hollow ZnSnO3 nanospheres were synthesized by a hydrothermal method using ZnO nanospheres as the hard template and raw material simultaneously. The combined characterizations of X-ray diffraction (XRD), scanning electron microscope (SEM) and high-resolution transmission electron microscopy (HRTEM) confirmed the successful preparation of hollow ZnSnO3 nanospheres. The gas-sensing results indicated that the sensor made from hollow ZnSnO3 nanospheres exhibited high sensitivity, good selectivity, and stability to ethanol at a low operating temperature of 200°C. The sensitivity was about 32 and the response and recovery time were about 4 s and 30 s for 100 ppm ethanol, respectively. The enhancement in gas-sensing properties was attributed to the hollow nanostructures and high specific surface areas of ZnSnO3 .